SISTEM SKORING WOODBALL BERBASIS WEB DENGAN PERHITUNGAN OTOMATIS MENGGUNAKAN METODE WATERFALL - Nurun Nihayatur Rifqiyah Aulia; Arie Nugroho; Anita Sari Wardani (Jurnal Ilmiah Informatika, 2026)
The score recording process in woodball competitions is still commonly carried out manually using paper sheets, causing recording errors, delays in score recapitulation, and difficulties in managing match data. This study aims to develop a web-based woodball scoring system with automatic calculation to improve the accuracy and efficiency of score management during competitions. The system was developed using the Waterfall method and implemented using PHP, MySQL, HTML, CSS, JavaScript, and Bootstrap. The application provides features such as player management, match management, real-time score input, automatic score calculation, ranking generation, and match result reporting. Based on Black Box Testing results, all system features functioned properly according to user requirements. The developed system is able to reduce manual calculation errors, accelerate score recapitulation, and support real-time monitoring of match results. Therefore, the system can be used as an effective digital solution for woodball match scoring and management.